The Family Role in Visionary Leader Recruitment Planning (Case Study in Family Company PT. DWI PRIMA REZEKY) - Dwiky Fitriansyah Pahlawan; Galuh Artika Suri; Eka Fenty Istiawati; Hadi Supratikta (Indonesian Development of Economics and Administration Journal, 2023)
Planning for the recruitment of company leaders is the process of preparing leaders and also key positions in the next generation in accordance with adequate skills and competencies and placing the right family members at the right time for the sustainability of the family company organization. The purpose of this study was to determine the role of family members in planning the recruitment of visionary leaders in family companies, namely PT. Dwi Prima Rezeky. The technique for determining informants was taken by means of purposive sampling using three respondents and analyzed qualitatively. The research results obtained are PT. Dwi Prima Rezeky has prepared and planned the recruitment of visionary leaders and family factors where the prospective leaders have completed the final stage of formal education, informal education, in-company training, work experience outside the company and there is support from family members who assist prospective leaders. to be better prepared to run the company.